The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnagi.2022.864128
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Parity With Change in Global Cognition and Incident Cognitive Impairment in Older Women

Abstract: BackgroundThe evidence of the association between parity and risk of mild cognitive impairment (MCI) or dementia is mixed, and the relationship between parity and longitudinal cognitive changes is less clear. We investigated these issues in a large population of older women who were carefully monitored for development of MCI and probable dementia.MethodsUsing the Women’s Health Initiative Memory Study, 7,100 postmenopausal women (mean age 70.1 ± 3.8 years) with information on baseline parity (defined as the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
2
0
0
Order By: Relevance
“…It was speculated that shorter cumulative endogenous estrogen exposure in women was associated with higher dementia risk. Other studies found no association between parity and cognition, or an opposite trend, that higher parity slowed the rates of cognitive decline 51,52 . We agree with Lead et al.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was speculated that shorter cumulative endogenous estrogen exposure in women was associated with higher dementia risk. Other studies found no association between parity and cognition, or an opposite trend, that higher parity slowed the rates of cognitive decline 51,52 . We agree with Lead et al.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies found no association between parity and cognition, or an opposite trend, that higher parity slowed the rates of cognitive decline. 51,52 We agree with Lead et al that "associations between fertility history and cognition were to large extent accounted for socioeconomic position, partly because this influenced health and social engagement". 28 There are some factors that only relate to women's cognitive decline.…”
Section: Male Rapid Decline Versus Stablesupporting
confidence: 83%
“…For instance, Heys and colleagues [27] reported significant associations between parity and verbal immediate and delayed verbal learning and memory, such that higher parity is associated with worse performance, while other studies found no association between parity and semantic fluency, verbal and working memory [29]. Direct comparisons with other studies, as well as incompatibility in results, could be due to several reasons, such as the sample country of origin (e.g., NHANES is a United States sample and may not be generalized to groups outside the United States) [27]; study design (cross-sectional versus longitudinal) and parity operationalization (continuous versus categorical variable with different levels) [24,25,28]. Regarding the latter, when we examined parity as a quadratic term, we observed a significant non-linear association between parity and verbal fluency, such that among Latina and NLW women, parity appears to be associated with lower scores on AF, particularly for women at the higher end of the parity range.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the literature on ADRD, evidence for the association between parity and cognition is more inconsistent, with some studies reporting that higher parity is associated with worse cognition [25][26][27], some reporting the opposite (i.e., higher parity is associated with better cognition) [28], and others reporting no significant associations [29]. Mental status (e.g., scores on the Mini-Mental State Exam [MMSE]) has repeatedly been associated with cognition: evidence of a detrimental effect of parity was detected in a large Chinese and smaller American cohort [27,30], yet in the Women's Health Study higher parity was associated with better mental status [28]. Parity has also been linked to cognitive performance in specific domains.…”
Section: Introductionmentioning
confidence: 84%